237 Antibiotic Prophylaxis of Precision Point Prostate Biopsy Under LA: Changed Practice in a District General Hospital. (28th February 2022) - Islam, F.; Saiyara, N.; Fazili, Z.; Shahid, J.
Abstract: Aim: More than 4 million prostate biopsies are performed worldwide each year (1) . Out of three different techniques (Template, transperineal, TRUS), Transperineal precision point biopsy under local anaesthesia is the latest and reported to have fewer infectious complications (2) . UTI, Urosepsis, septicaemia are some well-known infectious complications following prostate biopsies. Therefore, the Canadian Urological Association recommended the use of broad-based Gram-negative antibiotic prophylaxis 30 to 60 minutes before the procedure and continued for 2 to 3 days in their guideline (3) . Our aim was to compare the outcome of two different antibiotic prophylaxis regimens. Method: In our study to assess the outcome of single-dose prophylaxis compared to regular dose, we collected retrospective data of 119 patients who had undergone precision point biopsy in our hospital. Results: Among 119 patients, 52 (43.69%) were given 3 days of oral antibiotic followed by preprocedural dose and 67 (56.31%) were given just a single dose before the procedure. None of these patients from both groups were readmitted with any infectious complication post-procedure. 1 patient from the second group (single dose) was admitted with urinary retention but no increased inflammatory markers were found. Conclusions: TRUS biopsy breeches the rectal mucosa and carries higher chances of post-biopsy infection so requires antibiotic prophylaxis. Single-dose antibiotic prophylaxis is recommended option for transperineal biopsies as the infection rate is lower. Our study shows the same outcome for single-dose and 3-day regimens for transperineal precision point prostate biopsy. Moreover, the use of single dose will significantly reduce medicine costs and antibiotic resistance to improve patient compliance.